Federal Britain : a history - Kendle, John, 1937- (Routledge, 1997)
"In Federal Britain, John Kendle explores and analyses the British engagement with the federal idea from the early 1600s to the present day. The United Kingdom is faced with two major federal constitutional debates. The first is about the nations which comprise the British state and, hence, the division of power between Westminster and regional parliaments. The second surrounds the United Kingdom and the European Union. John Kendle sets these contemporary discussions in context in this book and provides valuable insights into their origins." "John Kendle argues that the federal idea has been a consistent feature for constitutional debate in the British Isles since the union of the crowns. In Federal Britain he examines the break-up of the first British empire and the development of modern federalism. As well as discussing the Anglo-Irish relationship and the United Kingdom's relationship to Europe, the author focuses on other contemporary issues such as the world order, imperial federation and decolonization. He considers the possibility of a rearrangement of constitutional relations within the United Kingdom." "Federal Britain outlines arguments for and against the adoption of the federal idea as a solution to either domestic or world problems. It is a timely addition to British constitutional thought and a thorough survey which will appeal to all historians and political scientists concerned with what offers the best potential government for a state."--Jacket